TOURISM DEVELOPMENT STRATEGY OF KAMPOENG KAJOETANGAN HERITAGE - Setiyawan Setiyawan (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
Kampoeng Kajoetangan - a historic area in Malang city and also business center during the Dutch colonial period until today. Many Dutch heritage buildings, including numerous residences in the Kampoeng Kajoetangan, have been kept in their original form. This is a prosperous area to become a tourist center. However, Kampoeng Kajoetangan need an improvement on management aspect. Therefore, we aim to analyze the strength, weakness, opportunity and also threat of this area and plan the best strategy to improve the tourism development of Kampoeng Kajoetangan. Descriptive qualitative with SWOT analysis was used in this study. This study found that SWOT quadrant position located in quadrant 1 and indicated by point (1.22;1.38). Those shows that Tourism Awareness Group (Pokdarwis) is highly possible to continue carry out the activities that they already have to increase growth and achieve maximum progress in marketing context. Power and opportunities strategy that was used in this study is marketing strategy with educative and persuasive approach. This approach has an important role in achieving a change of the community or local government negative mental attitude, especially from the mass media in order to more positively participate in actualizing the goals of developing tourism in Kampoeng Kajoetangan Malang.